Politeness strategies and speech acts used when handling problems during intercultural encounters: A case study of Thai cruise embarkation officers - Khuanmuang, Chariti; Wongthai, Nuntana (Kasetsart Journal of Social Sciences, 2026)
As cruise tourism is a global business requiring embarkation officers to communicate effectively, this study aimed to investigate politeness strategies and speech acts of Thai embarkation officers in handling problems during their intercultural encounters. Ten students majoring in Cruise Tourism performing embarkation duties at a Thai port-of-call were asked to complete a Discourse Completion Task (DCT) with six scenarios. The data were analyzed using the frameworks of politeness strategy (Brown & Levinson, 1987), speech acts (Searle, 1969), and intercultural communication (Hall, 1976; Hofstede, 2001). The study revealed that the participants utilized three types of politeness strategies: negative, bald, and positive, respectively. To display politeness, four types of speech acts were performed. Representative speech acts were used the most since the participants were required to follow regulations while still pleasing the passengers, so they referred to rules set by the company. Expressive speech acts were used when they showed sympathy to passengers by apologizing. Commissive speech acts were utilized to order to promise that they would solve the problems at hand. Directive speech acts were also found since the participants were required to directly ask passengers to do what was needed. The participants were able to alter their behavior from that found in a high context culture, using the type of direct responses that their Western passengers from low-context cultures use when communicating. The study’s findings may assist educational institutions countrywide in preparing their graduates to function as effective communicators in global communication contexts.